OPTIMIZATION OF INTERNATIONALIZATION PROGRAM OF BIOLOGY PROGRAM FMIPA UNNES WITH UTM MALAYSIA - Purwantoyo, Eling; Peniati, Endah; Rudyatmi, Ely; Avriana, Lilih; Sukmawati, Sukmawati (FMIPA UNNES, 2019)
Internationalization Programs of the Biology study, Semarang State University (UNNES), in order to realize the vision of UNNES as an international conservation university, continues. The objective of this study is to conduct internationalization program for Biology study in the form of student mobility, Credit transfer, guest lecturer, and world-class professor at UTM. This study is an Operational Research (OR). Operational Research is a research that aims to resolve operational problems, which result is used to help solving problems using scientific methods. UNNES Biology study proposes activities in the form of student mobility, credit transfer, guest lecturer, and world-class professor for Biology Student, but then the credit transfer is not done. The results obtained from the student mobility will be the topic at a public lecture from the Biology studies program. Student mobility program is an excellent opportunity for students to have the experience and knowledge at the international level.